Effect of the Flipped Classroom Learning Model on SBDP Learning Outcomes in Third Grade - Maria Simbolon; Canni Loren Sianturi; Melvin M. Simanjuntak (CV Putra Publisher, 2025)
This research aim For know the influence of the flipped classroom learning model on results Study art culture and crafts ( SBdP ) in class III of SD Negeri 091263 Pematangsiantar. This research use approach quantitative with type Pre-Experimental Design research through One Group Pretest-Posttest design. The research was conducted on students class III with amount sample as many as 22 students. The data collection technique used in study This in the form of tests, namely pretest and posttest. Before used in research, instruments question moreover formerly tested validity, reliability, level difficulty, and power differentiator. Based on validity test results of 40 grains of the questions tested, 20 items were obtained questions that are declared valid and appropriate used as instrument research. Reliability test results show Cronbach's Alpha value of 0.957 which is included in very high category, so instrument stated reliable and consistent used in research. In addition, the results of the level test difficulties show part big question is in the category moderate and easy, whereas power test results differentiator show question is in the category sufficient, good, and very good. Implementation study started with administering a pretest for know ability beginning student before given treatment. The pretest results show an average value of student of 57.50 with mark highest 70 and value lowest 45. Of the 22 students, only 2 students or 9% who reached completeness studying, while 20 students or 91% not yet reach completeness. Condition the show that results Study Arts and Culture student Still classified as low. After that, the researcher implementing the flipped classroom model in the learning process SBdP. This model used For help student understand material in a way more easy, interesting, and increase activeness and motivation student during the learning process ongoing. After implementing the flipped classroom model, the posttest results showed existence improvement results significant learning. The average posttest score of students increase to 91.36 with mark highest 100 and value lowest 85. All student or 100% has been reach completeness learning. The results of the N-Gain test show the average value is 0.8107 or 81.07% which is included in category high. This is show that The use of the flipped classroom learning model is very effective in increase results Study SBdP. In addition, based on t-test results obtained t - value namely 42.264 while the t table namely 2,080 at the level significant 0.05, so obtained t count > t table. Then it can be concluded that Ho is rejected and Ha is accepted, which means there is influence the use of the flipped classroom learning model results Study Arts and Culture in Grade III of SD Negeri 091263 Karang Sari